2006
DOI: 10.1002/pssc.200565446
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of InGaN‐based light emitting structures on silicon substrates with strain optimized buffer layers using long Al pre‐deposition

Abstract: GaN/InGaN multi quantum wells (MQWs) were grown on silicon (Si) substrates by Metalorganic Vapor Phase Epitaxy (MOVPE). A structure of layers consisting of AlN, AlGaN and GaN was used for subsequent deposition of the MQW structures on Si substrates. The Al pre-deposition time before growing the buffer structure and its effect on the formation of cracks was investigated. The emitted wavelength of the structure was changed by varying the thickness of the Mg-doped AlGaN electron blocking layer, by reducing the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Liu et al [18] reported that the substrate was exposed to trimethylaluminum (TMAl) for 10 s in order to prevent the formation of a Si x N y layer. Clames et al [19] reported predeposition of Al could reduce the crack in the GaN layer.…”
Section: Introductionmentioning
confidence: 98%
“…Liu et al [18] reported that the substrate was exposed to trimethylaluminum (TMAl) for 10 s in order to prevent the formation of a Si x N y layer. Clames et al [19] reported predeposition of Al could reduce the crack in the GaN layer.…”
Section: Introductionmentioning
confidence: 98%